A Critical Review of Assessments of Creativity in Education. Issue 1 (March 2022) - Long, Haiying; Kerr, Barbara A.; Emler, Trina E.; Birdnow, Max
This chapter provides a systematic, synthesizing, and critical review of the literature related to assessments of creativity in education from historical, theoretical, empirical, and practical standpoints. We examined the assessments used in the articles focusing on education that are published from January 2010 to May 2021 in eight creativity, psychological, and educational journals. We found that the assessments of creativity in education are split between psychological and education research and have increased international participation. Additionally, these assessments are more general than specific and focus more on cognitive than noncognitive aspects. Like previous reviews of assessments of creativity in general, this review showed that creativity in education is still mainly assessed by divergent thinking or creativity tests, self-report questionnaires, and product-based subjective techniques. We analyzed the benefits and drawbacks of each approach and highlighted many innovations in the assessment. We further discussed how the major assessment approaches address race, ethnicity, class, and gender issues in education. We concluded the review with recommendations for how to better assess creativity in education and how assessments of creativity in education contribute to our understanding of the creative educational experience and democratizing education.